Dynamic balance in elite karateka - Zago, M.; Mya, C.; Mapelli, A.; Francesca Shirai, Y.; Ciprandi, D.; Lovecchio, N.; Galvani, C.; Sforza, C. (Journal of Electromyography and Kinesiology, 2015)
In karate, balance control represents a key performance determinant. With the hypothesis that high-level athletes display advanced balance abilities, the purpose of the current study was to quantitatively investigate the motor strategies adopted by elite and non-elite karateka to maintain balance control in competition. The execution of traditional karate techniques (kihon) in two groups of elite Masters (n = 6, 31 ± 19 years) and non-elite Practitioners (n = 4, 25 ± 9 years) was compared assessing body center of mass (CoM) kinematics and other relevant parameters like step width and angular joint behavior.